Personalised, Contextualised Professional Learning Development: Putting it into Practice - Hazel Owen (Flexible Learning Association of New Zealand, 2011)
Research, such as that collated as part of the New Zealand Ministry of Education's (MoE) Iterative Best Evidence Synthesis (BES), indicates that regular Professional Learning and Development (PLD) for educators can have a positive effect on the quality of teaching and, in turn, on outcomes for diverse students. PLD, though, needs to offer flexibility of choice, time and approach, and to value personal theories and experiences. Learning should be accessible (both physically and design-wise), cumulative and relevant, and couched within an active community of practice (CoP). A pilot to develop a Virtual Professional Learning and Development (VPLD) model that offered personalised, contextualised PLD was initiated by the New Zealand MoE. The project focused on primary and secondary school teachers, although one tertiary teacher participated. This paper provides an overview of the VPLD pilot (2009-2010) while also synthesising main findings from the in-depth evaluation conducted during the pilot and summarising some of the lessons learned. In brief, results suggest that there are affordances built into the VPLD model that encourage and enable education practitioners to develop at their own pace, in a supported, supportive environment, with access to all that they need to scaffold their learning journey. Thus, if it is accepted that student outcomes can mirror practitioner performance (although this is a somewhat simplistic relationship), it would follow that, if practitioners can be mentored and guided in their own continual development and thinking around learning and teaching, there is potential for the overall learning experience for students to be enhanced.